Continued growth in the world economy - Günter Großer; Günter Weinert (Intereconomics, 1989)
After the stock market crash in the autumn of 1987 even optimists were predicting a sharp slowdown in the growth of the world economy in 1988. In the event, the GNP of the industrialised countries increased by 4% in real terms last year. What is the outlook for 1989?
Keywords: 330; Economic Trends